An Empirical Analysis of State and Private Sector Provision of Water Services in Africa - Kirkpatrick, Colin; Parker, David; Zhang, Yin-Fang (Published by Oxford University Press on behalf of the World Bank, 2014)
Under pressure from donor agencies and international financial institutions such as the World Bank, some developing countries have experimented with the privatization of water services. This article reviews the econometric evidence on the effects of water privatization in developing economies and presents new results using statistical data envelopment analysis and stochastic cost frontier techniques and data from Africa. The analysis fails to show evidence of better performance by private utilities than by state owned utilities. Among the reasons why water privatization could prove problematic in lower-income economies are the technology of water provision and the nature of the product, transaction costs, and regulatory weaknesses.